2015
DOI: 10.1038/cddiscovery.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy limits proliferation and glycolytic metabolism in acute myeloid leukemia

Abstract: Decreased autophagy contributes to malignancies; however, it is unclear how autophagy has an impact on tumor growth. Acute myeloid leukemia (AML) is an ideal model to address this as (i) patient samples are easily accessible, (ii) the hematopoietic stem and progenitor cells (HSPC) where transformation occurs is well characterized and (iii) loss of the key autophagy gene Atg7 in HSPCs leads to a lethal pre-leukemic phenotype in mice. Here we demonstrate that loss of Atg5 results in an identical HSPC phenotype a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
176
3
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(191 citation statements)
references
References 54 publications
6
176
3
6
Order By: Relevance
“…Previous studies have shown that autophagy limits some cells proliferation [42]. However, whether autophagy affects MSC proliferation remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that autophagy limits some cells proliferation [42]. However, whether autophagy affects MSC proliferation remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…While this suggests elevated autophagy in stem cells at a genetic level, functional evidence confirms highest autophagy in HSCs and generally declining levels as progenitors increasingly commit to lineages [24,28]. High autophagy levels in murine HSCs as measured by the autophagosome-specific dye CytoID and LC3-II colocalization with lysosomal LAMP-1+/À flux inhibitor BafilomycinA1 in GFP-LC3 transgenic mice by imaging flow cytometry was also paralleled in human HSCs [28]. It is tempting to speculate that high activity of autophagy or mitophagy is uniquely crucial in highly quiescent cells as they are unable to dilute damaged mitochondria and ROS quickly to their daughter cells.…”
Section: Proteostasismentioning
confidence: 99%
“…Using human AML bone marrow mononuclear cells and an AML mouse model, Watson et al54 showed that autophagy limits glycolytic metabolism in the AML context. Our data show that increased glycolytic dependence is associated with a reduced autophagy flux (Figure 3), while a diminished glycolytic metabolism, as observed in KG‐1 cells (Figure 1), was accompanied by elevated autophagy flux (Figure 3).…”
Section: Discussionmentioning
confidence: 99%